Deposition of strontium-90 in soil and vegetation at various locations surrounding the Fukushima Daiichi Nuclear Power Plant - Ball, Joseph E., author; Steinhauser, Georg, advisor; Brandl, Alexander, committee member; Gudmestad, Robert, committee member (Colorado State University. Libraries, 2015)
As a result of the 2011 Honshu earthquake, a tsunami formed off the coast of Japan that overtook the Fukushima Daiichi Nuclear Power Plant (FDNPP). This tsunami caused a cooling system failure at FDNPP. Due to this failure, a meltdown and subsequent release of radioactivity occurred. This project attempts to determine if 90Sr was released during the meltdown and could be detected in the surrounding environment. Vegetation and soil samples were collected from eight locations near the FDNPP ranging from 0 km to 40 km. The samples were subjected to a radiochemical separation to isolate 90Sr from other potential radionuclides in the samples. This was done to eliminate interference from those radionuclides in our analysis of 90Sr in the Hidex 300SL liquid scintillation counter (LSC). Results of the analysis determined with 95% confidence that 90Sr was detectable in both vegetation and soil samples within 4.1 km of the FDNPP. The highest levels of 90Sr activity concentration fall in-between the activity concentrations of naturally-occurring radionuclides in the earth's upper crust and do not pose a significant health threat to humans due to ingestion.